1998
DOI: 10.1536/ihj.39.659
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Utilization and Hemodynamic Response during Exercise in Children after Fontan Procedure.

Abstract: SUMMARYEight patients, 9.1 to 16.5 years of age, were studied 2.8 to 8.5 years after Fontan operation. Oxygen utilization was determined during upright bicycle exercise. The cardiac index and stroke index were measured by echocardiography and the anaerobic threshold was determined. The results were compared with 10 patients after surgical closure of the atrial septal defect. Anaerobic threshold (AT) in Fontan patients was lower than in the control subjects. Oxygen consumption at each stage of exercise was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…[3][4][5][6][7][8][9] While the maximal exercise capacity of children with congenital heart disease has been studied, 10 little is known about the levels of habitual physical activity, especially after the Fontan procedure. [11][12][13] Only one study 12 objectively quantified habitual physical activity levels by accelerometry, and another case study used a heart rate monitor.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9] While the maximal exercise capacity of children with congenital heart disease has been studied, 10 little is known about the levels of habitual physical activity, especially after the Fontan procedure. [11][12][13] Only one study 12 objectively quantified habitual physical activity levels by accelerometry, and another case study used a heart rate monitor.…”
mentioning
confidence: 99%
“…17 Two studies reported significantly decreased submaximal heart rate response, 28,31 and it was suggested by Banks et al 28 that paediatric Fontan patients may experience enhanced submaximal exercise efficiency relative to healthy individuals. Miyairi et al 23 reported that the heart rate response is similar to controls until patients reach the anaerobic threshold and significantly lower at the peak work load. Two studies examined Fontan aortic haemodynamics and found increased pulse wave velocity 26 or ratio in the backward-to-forward compression waves, 32 suggesting greater VO 2 at (V)AT (% predicted) 67 AE 14 72 -96 AE 25 25 25,27,44,68,70,72,73 The table excludes studies that reported these parameters as medians and interquartile ranges, rather than as means.…”
Section: Cardiovascular Response and Exercise Capacitymentioning
confidence: 96%
“…Reported mean VO 2peak values ranged from 14.4 AE 6.1 mL/kg/min 17 to 35.97 AE 6.84 mL/kg/min, 18 and mean percent-predicted VO 2peak values ranged from 54.3% AE 9.2% 19 to 86% AE 19% 20 (Table 1). Multiple studies reported significantly lower VO 2peak , 17,18,[21][22][23][24] VO 2 at anaerobic threshold, 17,23,25 and O 2 pulse 17,21 relative to healthy individuals. Although reductions in both maximal and submaximal exercise capacity have been reported, 26 submaximal exercise parameters are typically less reduced than those for maximal exercise.…”
Section: Cardiovascular Response and Exercise Capacitymentioning
confidence: 98%
See 1 more Smart Citation
“…Growth retardation, decreased exercise tolerance, and reduced activity levels are common is survivors of both palliative surgery [54][55][56] and transplantation [56][57][58][59][60][61]. Children who undergo either surgical option are at substantial risk of pain and anxiety related to procedures, and children often require frequent and prolonged hospital admissions for complications and for post-transplant cardiac biopsies.…”
Section: Other Considerations For Surgerymentioning
confidence: 99%